Chapter Geology, Textural Study, Ore Genesis and Processing of the Tabuaço Tungsten Deposit (Northern Portugal) - Foucaud, Yann (InTechOpen, 2018)
The Tabuaço tungsten deposit (Northern Portugal) is hosted in the Cambrian Douro Group metasediments, at the northern margin of the Beira-Tabuaço granitic complex. The hosting schisto-calcareous Lower Cambrian Bateiras Formation underwent a contact metamorphism induced by the intrusion of the granitic complex. The skarnification led to the crystallisation of scheelite (CaWO4). Two different skarn facies are encountered: 'Lower Skarn' and 'Main Skarn' both corresponding to the exoskarn. The 'Main Skarn' is mainly composed of vesuvianite (Ca10Mg2Al4(SiO4)5(Si2O7)2(OH)4), feldspars and fluorite. Zoisite, grossular, fluorapatite and scheelite are also present, as well as malayaite and cassiterite. Scheelite is disseminated and often occurs in association with fluorite, albite and vesuvianite. The 'Lower Skarn' level contains predominantly diopsidic pyroxene, quartz, zoisite, grossular and feldspars. Scheelite appears both laminated and disseminated, in association with fluorite and vesuvianite in minor proportions. The 'Main Skarn' is located in the Garnet, Pyroxene zone, while the 'Lower Skarn' corresponds to the Pyroxene, Garnet zone. Pyroxene has a global hedenbergite Hd40 composition. A major phase of albitisation destabilised fluorite, scheelite, vesuvianite, garnet and pyroxene. A late stage of chloritisation is associated with the exhumation. The processing of the Tabuaço ore has been adapted to the Ca-bearing rich paragenesis and to the scheelite mean size.